Analysis of Students’ Difficulties in Solving Story Problems in Terms of Cognitive Style - Nia Purwosari; Muhammad Jamaluddin (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2024)
The purpose of this study was to describe the difficulty of students in solving story problems in terms of cognitive style. Indicators of difficulty in the study are students' difficulties in using concepts, students' difficulties in using principles, and students' difficulties in solving verbal problems. The method used in this research is descriptive qualitative. The data collection techniques used were written tests and interview techniques. The results showed that field-dependent subjects were able to understand concepts and were able to use principles, field-dependent subjects tended not to be able to solve verbal problems and had difficulty not being able to understand what was known and not being able to understand the form of mathematical models. While field-independent subjects can understand concepts and can use principles, field-independent subjects tend not to be able to solve verbal problems and have difficulty not being able to understand what is known in the problem